2022-RA-1515-ESGO Impact of surgical staging on survival of low grade endometrioid ovarian cancer apparently confined to the ovary. (20th October 2022) - Bizzarri, Nicolò; Imterat, Majdi; Fruscio, Robert; Perrone, Anna Myriam; Mancari, Rosanna; Traut, Alexander; Rosati, Andrea; Bois, Andreas du; Ferrari, Debora; de Iaco, Pierandrea; Ergasti, Raffaella; Ataseven, Beyhan; et al.
Abstract : Introduction/Background: To assess the disease-free survival (DFS) of patients with low-grade endometrioid ovarian cancer apparently confined to the ovary, according to surgical staging. Secondary endpoint was to evaluate the DFS according to adjuvant chemotherapy. Methodology: Multicenter, retrospective, observational cohort study. Patients with endometrioid ovarian carcinoma, surgical procedure performed between 05/1985–12/2019, stage pT1 N0/N1/Nx Grade 1–2 were included. Patients were stratified according to completeness of surgical staging (complete defined as peritoneal and retroperitoneal staging), lymphadenectomy (defined as removal of any lymph node (LN) versus no LN assessment), and receipt of adjuvant chemotherapy. Results: 298 patients were included in the study period. 166 (55.7%) patients underwent complete surgical staging, and 199 (66.8%) patients underwent LN assessment (of these, 166 -83.4%- had unilateral/bilateral pelvic and para-aortic/caval lymphadenectomy). 11 (5.5%) patients of those undergoing LN assessment showed pathologic metastatic LNs (FIGO-stage IIIA1). 9/11 (81.8%) were diagnosed with grade 2 endometrioid ovarian cancer. 155 (52.0%) underwent adjuvant chemotherapy. Median follow up time was 45 months (95%CI:37.5–52.5). 5-year DFS and overall survival of the entire cohort were 89.8% and 96.2%, respectively. Patients undergoing complete surgical staging had a trend toward a better 5-year DFS comparing to incomplete surgical staging (92.4% versus 86.5%, respectively;p=0.051). Performance of lymphadenectomy (sampling/systematic) was associated with better 5-year DFS compared to no lymphadenectomy (91.9% versus 85.6%, respectively;p=0.016) ( figure 1 ). Adjuvant chemotherapy did not impact 5-year DFS (p=0.552). At univariate analysis the only significant variable affecting DFS was the performance of lymphadenectomy (HR:0.388; 95%CI:0.174–0.866;p=0.021). Conclusion: In a retrospective multicenter series of low-grade endometrioid ovarian cancers apparently confined to the ovary, lymphadenectomy appeared to be associated with improved DFS. Adjuvant chemotherapy did not impact DFS. Nevertheless, the present results derive from a retrospective uncontrolled study, in which the indication for or against lymphadenectomy/adjuvant chemotherapy was not prospectively defined, causing potential significant selection bias.